2018
DOI: 10.1159/000489861
|View full text |Cite
|
Sign up to set email alerts
|

Partially Hydrolyzed Whey Infant Formula: Literature Review on Effects on Growth and the Risk of Developing Atopic Dermatitis in Infants from the General Population

Abstract: Limited evidence is available regarding the effect of partially hydrolyzed whey-based formula (pHF-W) on growth and atopic dermatitis (AD) risk reduction in infants within the general infant population, and without a familial history of allergy as an inclusion or exclusion criterion. We reviewed the current evidence available from studies using pHF-W in the general population and summarized the data on safety (growth) and efficacy outcomes (reduction of AD), comparing the studies side by side. A total of 8 cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…Other data from the GINI study showed that there was no significant difference in BMI ( z score) of infants fed with 100% pHF-W in the first 4 months of life compared with those fed with standard CMF for up to 10 years [25]. Eight clinical trials were included in a recent review, seven of which used the same pHF-W [26]. Six out of 8 studies indicated a reduction in atopic manifestations using a specific pHF-W versus CMF in the first years of life [26].…”
Section: Phf For All Nonbreastfed Babiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other data from the GINI study showed that there was no significant difference in BMI ( z score) of infants fed with 100% pHF-W in the first 4 months of life compared with those fed with standard CMF for up to 10 years [25]. Eight clinical trials were included in a recent review, seven of which used the same pHF-W [26]. Six out of 8 studies indicated a reduction in atopic manifestations using a specific pHF-W versus CMF in the first years of life [26].…”
Section: Phf For All Nonbreastfed Babiesmentioning
confidence: 99%
“…Eight clinical trials were included in a recent review, seven of which used the same pHF-W [26]. Six out of 8 studies indicated a reduction in atopic manifestations using a specific pHF-W versus CMF in the first years of life [26]. The literature review confirmed that pHF-W supports normal growth in infants and suggests that the risk of AD may be reduced in not-fully breastfed infants when supplemented with a specific pHF-W during the first 4–6 months of life [26].…”
Section: Phf For All Nonbreastfed Babiesmentioning
confidence: 99%
“…A recent study using a freshly prepared puree of cow’s milk, egg yolk, egg white, and soy, provided high sensitivity and specificity as well as positive and negative predictive values, illustrating that the atopy patch test is a valuable diagnostic test for food allergy in patients without specific IgE [33]. A recent literature review investigating the efficacy and safety of a partially hydrolyzed whey-based formula in the general population concluded that it supports normal growth in infants, and may reduce the risk of AD in infants who are not fully breastfed as compared to infants receiving a cow’s milk formula during the first 4–6 months of life [34]. Another study correlated 25-hydroxyvitamin D levels in umbilical cord blood and serum of infants with the development of allergic sensitization and diseases in early childhood.…”
Section: Understanding the Pathogenesis Of Atopic Dermatitismentioning
confidence: 99%
“…However, this seemed doubtful for prevention under recent negative outcomes of PHF, even in high-risk infants. Second, they showed a literature review of studies using PHF in the general population (for which a family history of allergy was neither an inclusion nor an exclusion criterion), which indicated a reduction in atopic manifestations on using a specific PHF compared with standard formula in the first years of life [10]. However, numerous limitations to these studies were identified, and this study was also industry-supported.…”
mentioning
confidence: 99%
“…However, numerous limitations to these studies were identified, and this study was also industry-supported. Third, they mentioned that PHF meets all nutritional requirements and supports normal growth [10]. However, the long-term data of PHF in healthy infants on growth, body composition, hormonal responses, and serum metabolites are limited, although no data suggest that PHF is potentially harmful for healthy term infants.…”
mentioning
confidence: 99%